Manual on uniform traffic control devices : for streets and highways (ATSSA/ITE/AASHTO, 2003)
The Manual of Uniform Traffice Control Devices (MUTCD) is aproved by the Federal Highway Administrator as the National Standard in accordance with Title 23 U.S. Code, Sections 109(d), 114(a), 217, 315, and 402(a), 23 CFR 655, and 49 CFR 1.48(b)(33), and 1.48(c)(2).